COVID-19 y TIC: estrategias pedagógicas y desigualdades educativas en clave institucional - Dabenigno , Valeria (Universidad Nacional del Litoral, 2021)
Based on an online survey conducted in April/May 2020, this article analyses the pedagogical strategies using ICT that were applied by secondary school teachers in the province of Buenos Aires at the beginning of the lockdown caused by the COVID-19 pandemic. We examine the relationship between these strategies and educational inequalities, considering both macro/structural variables (school management and students’ socioeconomic level) and meso-social variables (school reputation, degree of ICT use at institutional level, and institutional responses to demands for pedagogical continuity). First, we depict how schools were using ICT before the pandemic, since this provides unequal starting points to produce a response to pedagogical continuity policies, which were interpreted as a forced virtualization of teaching. Secondly, we examine different facets of teachers’ pedagogical strategies, such as frequency of assignments, the means used to do so, and the aims of teachers’ online interactions with students. Finally, we explore teachers’ perceptions of their students’ difficulties to deal with the proposed educational tasks and activities.